2011
DOI: 10.1007/s10895-011-0835-1
|View full text |Cite
|
Sign up to set email alerts
|

Azonium-Ammonium Tautomerism and Inclusion Complexation of 1-(2,4-diamino phenylazo) Naphthalene and 4-aminoazobenzene

Abstract: Spectral characteristics of 1-(2,4-diamino phenylazo) naphthalene (FBRR, fat brown RR) and 4-aminoazobenzene (AAB) have been studied in various solvents, varying hydrogen ion concentrations and in β-cyclodextrin (β-CD). The inclusion complex of FBRR and AAB with β-CD were analysed by UV-visible, fluorometry and CAche-DFT methods. Solvent study reveals that only azo tautomer is present in both compounds and the large red shifted absorption and emission maxima of FBRR indicate naphthalene ring effectively increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…The observed spectral changes are interpreted in terms of azo-hydrazo equilibrium. [24][25][26][27] The above results confirmed that increasing the polarity of solvents leads to larger amount of the 'hydrazo' form, than that of the 'azo' form. [32,33] The spectral maxima also show that methyl substituent hardly affects the position of the azo-hydrazo tautomeric equilibrium compared to hydroxyl substituent.…”
Section: Effect Of Solventsmentioning
confidence: 66%
See 4 more Smart Citations
“…The observed spectral changes are interpreted in terms of azo-hydrazo equilibrium. [24][25][26][27] The above results confirmed that increasing the polarity of solvents leads to larger amount of the 'hydrazo' form, than that of the 'azo' form. [32,33] The spectral maxima also show that methyl substituent hardly affects the position of the azo-hydrazo tautomeric equilibrium compared to hydroxyl substituent.…”
Section: Effect Of Solventsmentioning
confidence: 66%
“…The small increase in the absorption with the addition of both CDs has been attributed to the improved dissolution of the guest molecules through the detergent action of CDs. [24][25][26][27][28] Emission spectra monitored at two different excitation wavelengths (350 and 510 nm) are displayed in Figures 3 and 4. The emission spectra at λ exc $ 350 nm are different than that at λ exc $ 510 nm.…”
Section: Molecular Modelling Studiesmentioning
confidence: 99%
See 3 more Smart Citations